2023
DOI: 10.1038/s41598-023-32110-9
|View full text |Cite
|
Sign up to set email alerts
|

Label-free liquid biopsy through the identification of tumor cells by machine learning-powered tomographic phase imaging flow cytometry

Abstract: Image-based identification of circulating tumor cells in microfluidic cytometry condition is one of the most challenging perspectives in the Liquid Biopsy scenario. Here we show a machine learning-powered tomographic phase imaging flow cytometry system capable to provide high-throughput 3D phase-contrast tomograms of each single cell. In fact, we show that discrimination of tumor cells against white blood cells is potentially achievable with the aid of artificial intelligence in a label-free flow-cyto-tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Finally, single-cell and protein biology assayed by flow cytometry can also be linked to ML in NB. For example, a study found that using ML, it is possible to provide tomographic imaging and 3D phase-contrast tomograms on single NB cells separated by flow cytometry [ 66 ], a promising method for easier detection of NB.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, single-cell and protein biology assayed by flow cytometry can also be linked to ML in NB. For example, a study found that using ML, it is possible to provide tomographic imaging and 3D phase-contrast tomograms on single NB cells separated by flow cytometry [ 66 ], a promising method for easier detection of NB.…”
Section: Discussionmentioning
confidence: 99%
“…A diagnostic concept known as “liquid biopsy” has emerged, primarily involving the detection of tumor fragments that have shed into the circulatory system through the analysis of body fluids such as blood and urine. These fragments can be identified and isolated from the blood using high-throughput methods, allowing for subsequent analysis at the single-cell level ( 115 , 116 ). Compared to traditional diagnostic techniques, liquid biopsy is an attractive non-invasive method for tracking disease progression in real time ( 117 , 118 ).…”
Section: Liquid Biopsymentioning
confidence: 99%
“…They were able to classify various drug-resistant cancer cells and differentiate cancer cells from monocytes. 42,43 Some researchers have employed digital holographic flow cytometry to image the urine samples, subsequently performing phase reconstruction of red blood cells, white blood cells, and crystals in urine. 44,45…”
Section: Introductionmentioning
confidence: 99%